Changes in margin re‐excision rates: Experience incorporating the "no ink on tumor" guideline into practice. Issue 8 (27th July 2017) - Patten, Caitlin R.; Walsh, Kendall; Sarantou, Terry; Hadzikadic‐Gusic, Lejla; Forster, Meghan R.; Robinson, Myra; White, Richard L.
Abstract : Introduction: Prior to the "no ink on tumor" SSO/ASTRO consensus guideline, approximately 20% of women with stage I/II breast cancers undergoing breast conservation surgery at our institution underwent margin re‐excision. On May 20, 2013, our institution changed the definition of negative margins from 2 mm to "no ink on tumor." Methods: A retrospective review was conducted of patients who had surgery at our institution with clinical stage I/II breast cancers between June 1, 2011 and May 1, 2015. In the pre‐guideline cohort (pre) and post‐guideline cohort (post), negative margins were 2 mm and "no ink on tumor, " respectively. Results: Implementation of the guideline resulted in a significant decrease in the positive/close margin rate (29.6% pre vs 10.1% post; P  < 0.001) and numerical decrease in re‐excision rate (20.4% pre vs 16.3% post; P  = 0.104). No significant difference was found in local recurrence between the cohorts with limited follow‐up (1.2% pre vs 1.5% post; P  = 0.787). Conclusion: The implementation of the "no ink on tumor" guideline at our institution has resulted in a significant decrease in positive margin rates and a numerical decrease in margin re‐excisions. In addition to margin status, surgeons continue to use individual patient and histologic factors to decide for or against margin re‐excision.